Effect of Women’s Role on Household Decision Making on Institutional Delivery of the recent Child in Nepal - Adhikari, Ramesh (Journal of Management and Development Studies, 2015)
Nepalese women are behind than men in many areas, such as educational attainment, participation in decision-making and health service utilization, all of which have an impact on reproductive health outcomes. This paper explores effect of women's role on household decision making on institutional delivery of the child in Nepal Data as drawn from the Nepal Demographic and Health Survey, 2011. The analysis is confined to women who had given birth in the five years preceding the survey (n=4,148). The net effect of women’s role on household decision making on institutional delivery after controlling for the effect of other predictors has been measured through multivariate logistic regression analysis. The findings indicate that institutional delivery was still very low in Nepal. Only two in five of the women (40%) had delivered their last child with health facilities. Notably, higher level of women’s role on household decision was associated with higher level of institutional delivery [adjusted odds ratio (aOR=1.20)] than their comparison group. It can be concluded that programs should aim to increase use of maternal health services by improving women’s role on household decision making so that the overall well-being of the family can be maintained and enhanced.